Kue Kopi (Ku-Kopi) Sebagai Produk Alternatif Olahan Kopi Berbasis Potensi Geoekonomi - Nasobi Niki Suma; Noviana Mariatul Ulfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The commodity of coffee in Indonesia was first recognized and brought by the Dutch to be cultivated on the island of Java. Coffee production in Indonesia is a superior product in several regions, including in Jember Regency, East Java. However, the abundant coffee production, unfortunately, is only sold for coffee or its raw materials. In addition, the main problems of coffee farmers include coffee quality, capital, and marketing. Even though the potential for coffee in Silo District is the largest supplier in Jember Regency, breaking the 40% mark. The research method uses Aset Based Community Development (ABCD) by utilizing geographical assets of regional natural resources and economic assets in the area of Pace Village, Silo District, Jember Regency. The goals in this community engagement are (1) knowing the potential of Pace Village, and (2) being able to make alternative products for processed coffee cakes. The results of community engagement, namely processed coffee products in the form of coffee cakes, are an alternative to increasing the economic value and potential branding of coffee in Pace Village.